Optimization of Oil and Methanol Ratio, Time, and Reaction Temperature of Biodiesel Making from Kemiri Sunan Oil (Trisperma Oil Reuteals) with Two Stage Transesterification - Pranita, Zahra Aumy; Paramita, Vita; Amalia, Rizka; Kusumayanti, Heny (Journal of Vocational Studies on Applied Research, 2020)
Biodiesel is an alternative fuel which is generally produced from the transesterification process between vegetable oil and methanol, ethanol, or butanol with the help of a catalyst which aims to speed up the reaction. The raw material for making biodiesel, namely renewable vegetable oil, also sees Indonesia as a tropical country so that biodiesel can be produced on a large scale and is environmentally friendly. Vegetable oil can be classified into two, namely edible oil (food) and non edible oil (non-food). The research was conducted using non-edible vegetable oil, namely kemiri sunan oil, which was carried out using a two-stage transesterification method. This research was conducted to determine the optimization of the ratio of oil and methanol (1: 4; 1: 5; 1: 6), temperature (55⁰C, 60⁰C, 65⁰C) and reaction time (15 minutes, 30 minutes, 45 minutes) in making biodiesel from kemiri sunan oil, where the experimental results obtained the highest yield value of 82.79%. In the experiment, analysis of density, viscosity, moisture content and cetane number was also carried out. The results showed that the viscosity and cetane number obtained did not meet SNI for biodiesel.